The effectiveness of video promotional media in implementing hand washing with soap at State Elementary School 04 Rantauprapat - Apriyani, Trisna; Astuty, Delfriana Ayu; Agustina, Dewi (Institute of Computer Science (IOCS), 2024)
Health problems that often occur in school-aged children are usually always related to cleanliness and the environment, one of which is the problem of washing hands with soap. Hands are the center for germs that cause disease. Hand washing is a form of personal hygiene carried out with the aim of preventing disease. Washing your hands with soap is a sanitation action by cleaning your hands and fingers using water and soap. The aim of this research is to determine the effectiveness or influence of health promotion media via video in the implementation of hand washing with soap (CTPS). This type uses quantitative research, with a pre-experimental research design, the research design used is One-Group. Pretest-Posttest Design. The sample used in this research consisted of 73 respondents from grades 5 and 6, with a sampling technique namely purposive sampling technique. The data analysis carried out was univariate and bivariate analysis, with the results of the Wilcoxon signed rank test statistical test obtained with ap value = 0.00 ≤ 0.05, which means that the hypothesis is accepted or there is an effect or influence from the video media of washing hands with soap on knowledge and attitude towards students. There is an influence of health promotion using video media on the knowledge and attitude of washing hands with soap among students at SD N 04 Rantauprapat.